Chinese patent medicines combined with hormone replacement therapy for premature ovarian failure: A Bayesian network meta-analysis - Zhong, Han-Zhi; Li, Mao-Ya; Yin, Xiao-Lan; Bin, Cheng-Li; Zhou, Si-Yun; Wei, Shao-Bin (Frontiers in Medicine, 2022)
Objective:: To compare the efficacy differences between Chinese patent medicines combined with hormone replacement therapy(HRT) in the treatment of premature ovarian failure(POF) by the Bayesian network Meta-analysis(NMA) method. Methods: Randomized controlled trials(RCTs) reporting Chinese patent medicine combined with HRT for POF included by Medline(via pubmed), Embase, Cochrane Library, China National Knowledge Infrastructure Database(CNKI), Wanfang Database(Wanfang), VIP Database(VIP), and China Biology Medicine Database(CBM) from the inception of the databases to July 2022. Two researchers independently screened the articles, extracted data, and evaluated the quality. The literatures that met the inclusion criteria were screened out, the quality and risk of bias of the included studies were assessed according to the Cochrane 5.1 manual and RevMan 5.4, and network meta-analysis was performed using Stata 15.1 and R software. Results: 64 RCTs involving 5,675 individuals containing 12 oral Chinese patent medicines combined with HRT were enrolled into current NMA. The results showed that when compared with patients using only HRT, total clinical response rate is greater in patients using HRT combined with one of this 12 oral Chinese patent medicines, and it has statistical significance. Among them, Zuogui pills+HRT (mean difference [MD] = 3.92; 95% credible interval [CrI] = 0.86, 23.84; SUCRA = 73.76%) is most likely to be the best intervention, and the suboptimal intervention is Guishen pills + HRT (MD = 3.22, 95%CrI = 1.16, 9.44, SUCRA = 70.60%). Conclusion: Chinese patent medicines combined with HRT were more effective than HRT alone in the treatment of POF. Zuogui pills is good at decreasing FSH and luteinizing hormone(LH), and more effective in the improvement of total clinical response rate; Xuefu Zhuyu Capsule is also good at decreasing FSH. Ziheche Capsule is expert in improving Estradiol level; Kuntai Capsule is doing well in increasing antral follicle count, and the lowest incidence of adverse reactions. However, the quality of the literature included in this study is relatively low, so it may affect the results of the study.Therefore, more higher quality and multi-center trial would be necessary for supporting these results.